Children's unspoken language - Doherty-Sneddon, Gwyneth, 1968- (J. Kingsley, 2003)
Gwyneth Doherty-Sneddon, a developmental psychologist and mother of a young son herself, demonstrates the way in which a young child's developing personality and intelligence is revealed in their non-verbal communication. She shows how parents and other adults have the potential to facilitate a child's social and intellectual growth through acknowledging and responding to this unspoken language. Taking an in-depth look at four of the channels of non-verbal communication - hand gesture, facial expression, eye gaze and touch - this accessible text follows the development of young children from b.